The dynamics of moonlightning: What is happening in the Russian informal economy? - Alessandra Guariglia; Byung-Yeon Kim (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This paper uses rounds 5 to 8 of the Russian Longitudinal Monitoring Survey (RLMS) to analyse the dynamics of moonlighting of working-age population.We find that moonlighting is transitory, and is generally associated with career shifts.Those respondents who expressed a desire to switch jobs in the past are in fact more likely to moonlight in the present, and to effectively switch jobs in the future.The career shifts tend to be towards self-employed activities.These results imply that the Russian secondary labour market, as part of the informal economy, can provide long-term benefits for the economy as an effective incubator for setting up new self-employed businesses.
URN:NBN:fi:bof-201408072000
Keywords: 330; Moonlighting; Informal economy; Labour supply